EXPERIENCE AND TRAINING RELATE TO PERFORMANCE CLEAN AND HEALTHY LIVING BEHAVIOR IN CADRE IN THE WORKING AREA OF POASIA PRIMARY HEALTH CARE, KENDARI CITY: CLEAN AND HEALTHY LIVING BEHAVIOR - Hasmariana Hasmariana; La Ode Saafi; Tasnim Tasnim; Anry Hariadhin Depu (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2021)
Background:Southeast Sulawesi Provincial data shows thatCommunity life behavior is measured by the number of households with a clean and healthy lifestyle which is assessed based on predetermined indicators. in 2015 the percentage of Clean and Healthy Living Behaviors was 45%, in 2016 there was an increase of 52% and decreased in 2017 by 49% and 2018 by 46%, for 2019 there was an increase in the percentage of 53% again.Based on these data the coverage is still low because the target set according to the minimum service standard is 80%. The orientation of community empowerment for health cadres is still insufficient, it is noted that only 36 people have received community empowerment training. The insufficient number of cadres can also make a negative contribution, resulting in the lack of achievement of the Puskesmas program Methods:This type of research is a quantitative study, with a cross sectional study approach. The population in this study amounted to 100 people and a sample of 80 all cadres in 20 Posyandu in the working area of ??Puskesmas Poasia, Kendari City. The sampling technique used in this study was simple random sampling. Result:Based onthe results of statistical tests show that the value (X2hit) = 0.286 <X2tab =3,841, meaning that there is no relationship between experience and performance of clean and healthy living behavior cadres, household structures and values ??(X2hit) = 15,556> X2tab =3,841, meaning that there is a relationship between training and the performance of clean and healthy living behavior cadres in household arrangements in the working area of ??Puskesmas Poasia, Kendari City. Conclusion:Cadres are expected to play an active role in increasing their knowledge and experience through training activities on cadre performance held by Puskesmas Poasia.